Stability of emergent time periodicity in a few-body interacting system - Steve Campbell; Jens Eisert; Giacomo Guarnieri (New Journal of Physics)
We examine the onset and resilience of emergent time periodicity in a few-body all-to-all interacting Lipkin–Meshkov–Glick model, where one of the constituents is locally in contact with a thermal bath. Employing both a collision model framework and a suitable time-continuous description, we show that stable time-periodic behavior can only be exhibited when the bath acts as a purely dissipative channel. We assess the role that the microscopic interactions within the system play, establishing that for the all-to-all model the introduction of temperature leads to a melting of the emergent time periodicity, in contrast to stable long-time behavior which can be maintained for nearest neighbor XXZ type interactions.